Analyses of human papillomavirus, Chlamydia trachomatis, Ureaplasma urealyticum, Neisseria gonorrhoeae, and co-infections in a gynecology outpatient clinic in Haikou area, China - Zhe Lu; Peizhen Zhao; Huijun Lu; Meifang Xiao (BMC Women's Health, 2023)
Abstract Background The purpose of this study was to study the infection rates of Chlamydia trachomatis (CT), Ureaplasma urealyticum (UU), Neisseria gonorrhoeae (NG), and co-infections with human papillomavirus (HPV) in a hospital gynecology outpatient clinic in the Haikou region in 2021. Methods From January to December 2021, the Women and Children Medical Center of Hainan Province collected 2389 samples of cervical exfoliated cells and vaginal swab specimens from gynecologic outpatients. The samples were then analyzed descriptively for data, and the detection rate of each pathogen was tallied. All vaginal swabs were obtained for CT, UU, and NG DNA testing, and cervical exfoliated cells for HPV genotyping. Analyses were performed on the detection rate of each group. Results In 2389 samples, the frequencies of pathogen identification among the 2389 samples were as follows: UU (58.43%); HPV (17.29%); CT (7.99%); and NG (0.38%). HPV, CT, UU, and NG were detected in 33.33%, 22.55%, 77.45%, and 2.94% of individuals between 15 and 20 years of age, respectively. The detection rates of CT, UU, and NG were substantially greater in the HPV-positive group than the the HPV-negative group (P < 0.05). Conclusion Among gynecologic outpatients at a hospital in the Haikou area, the probability of mixed infections with genital tract pathogens in HPV-positive patients was higher compared to HPV-negative patients. Reproductive tract infections are becoming more prevalent in younger people, hence adolescent sexual health education needs improvement.